Implementasi Kebijakan Retribusi Parkir Pasar Besar Guna Meningkatkan Pendapatan Asli Daerah Di Kota Madiun - Meti Kumala Oktisari; Khoirun Nisak (Niqosiya: Journal of Economics and Business Research, 2023)
The City of Madiun is one of the areas with quite a large potential for Regional Original Income, where one of the most significant potentials comes from parking fees; this sector is a primary source of revenue. The method and type of approach used in this research is to use a qualitative research method with a descriptive type. Two data are used in this study, namely primary and secondary data. Data collection techniques used by researchers are interviews, observation, and documentation. The results of this study show that the implementation of the Madiun extensive market parking fee policy has yet to be fully optimal, as seen from the retribution revenues in the big market that do not reach the specified target. According to George C. Edwards III, several indicators of policy implementation still need to be appropriate, including indicators of Resources and Disposition. The presence of illegal parking officers causes obstacles to the implementation of the parking levy policy, the levy rates not by the established policies, the limited number of Human Resources (HR), and the lack of public awareness and supporting factors for the implementation of the market parking levy policy is the existence of communication from the Department of Trade as the implementor of this policy by collaborating with inter-agencies, namely Satpol PP, parking managers, and parking officers in the joint operations carried out.